Interactions of Ofloxacin and Erythromycin with the Multidrug Resistance Protein (MRP) in MRP-Overexpressing Human Leukemia Cells - Terashi, Kenji (American Society for Microbiology, 2000)
To investigate interactions between the multidrug resistance protein (MRP) and antimicrobial agents, we examined the effects of 12 agents on vincristine sensitivity and efflux of the calcein acetoxy-methyl ester (calcein-AM) of a MRP substrate in MRP-overexpressing cells. Only ofloxacin and erythromycin enhanced sensitivity with increased intracellular vincristine accumulation and inhibited the calcein-AM efflux. Our findings suggest that the two agents are possible MRP substrates and may competitively inhibit MRP function as a drug efflux pump.